The impact of regional health care coverage on infant mortality and disease incidence - Helge Liebert; Beatrice Mäder (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
This paper investigates the effect of changes in the physician coverage ratio on infant and disease mortality, utilizing historical data from Germany. The results indicate substantial health effects. One additional physician per 1,000 of population reduces infant mortality by 23%. We find similar negative effects for a variety of common diseases and stillbirths. Using a semiparametric control function approach, we demonstrate that the marginal returns to coverage are nonlinear and decreasing.
Keywords: I10; I18; N34; 330